Development of Character Assessment Instrument on English Learning FOR Junior High School Students - Andi Abdurrahman Manggaberani; Nur Hidayanto Pancoro Setyo Putro (The Islamic Education and Multiculturalism Foundation, 2023)
This research endeavors to address a pressing need in education, specifically, the development of a robust character education assessment tool for junior high school students in the context of English subjects. The primary focus of this study is producing character education assessment instruments in English subjects for junior high school students with good construction. This study is a research and development using the ADDIE development model. The instrument development process consisted of the analysis stage, the design stage, development stage, implementation stage and evaluation stage. The instrument developed is an assessment instrument on English subjects in the form of self-assessment, analyzed using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). The instrument developed has met the validity and reliability requirements with the results of content validity shown by the Aiken index of 0.955 while the test results with CFA show the loading factor value on each item > 0.4 and the student character measurement model compiled is fit with the theorized model by proving the results of p-values = 0.056; CFI = 0.979; TLI = 0.972; RMSEA = 0.031; SRMR = 0.055 with the results of the reliability of the items in each dimension/factor > 0.7.